Pengembangan Aplikasi Pemantauan Kualitas Wi-Fi dengan Crowdsourcing berdasarkan Lokasi berbasis Android - I Made Setia Baruna; Agi Putra Kharisma; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Wi-Fi has become the main choice for universities as media to provide internet access, but the consequence is that the use of Wi-Fi has increased significantly, but the quality of the network is reduced. The high use of the internet also requires more tools to monitor the quality of the existing network, and also measuring and verifying the quality of the Wi-Fi networks is very difficult because there is no tool to cover all variables. From this problem, an application was developed to monitor quality of Wi-Fi, whose data was taken by crowdsourcing, where Wi-Fi quality data was collected from contributions of users who conducted the test. The collected data will be visualized into a heatmap to make it easier for users to find good quality Wi-Fi location. Heatmap can also be filtered based on time range and by download speed, upload speed, and ping. The application was designed in advanced for the functions, and then developed for Android system implemented with Kotlin programming language. The application has been tested with black box testing for testing validation functionality with valid result for all test cases, and received SUS score of 72 which shows a value above average for usability testing.